Medical Philanthropy's Effectiveness via Zakat Distribution: A Case Study at Hospital Canselor Tuanku Muhriz UKM - Muhamad Firdaus Ab Rahman; Hussein 'Azeemi Abdullah Thaidi; Azman Ab. Rahman; Mohd Izzat Amsyar Mohd Arif (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite